A New Combination of RAKE Receiver and Adaptive Antenna Array Beamformer for Multiuser Detection in WCDMA Systems - Shahriar Shirvani-Moghaddam; Hajar Sadeghi (International Journal of Antennas and Propagation)
The aim of this paper is to combine smart antenna beamforming and RAKE receiver in wideband code division multiple access (WCDMA). The proposed method combines spatial diversity as well as temporal diversity to improve the performance and overcome both interferences and multipath fading. This investigation has focused on one of the new proposed blind beamforming algorithms. It is based on constrained constant modulus (CCM) algorithm which is used for deriving a recursive-least-squares (RLS-) type optimization algorithm. We illustrate the comparison of bit error rate (BER) of the proposed receiver with simple correlator and also 1D-RAKE receiver in multiuser detection (MUD) WCDMA. The simulation results show that the proposed 2D-RAKE receiver offers lower BER rather than conventional ones, that is, it is an effective solution for decreasing the effect of interference and increasing the capacity, in a joint state.